Manajemen dan Mutu Pembelajaran Bahasa Indonesia Di SMP Negeri 4 Rejang Lebong - Yanto, Murni (Tadbir : Jurnal Studi Manajemen Pendidikan, 2018)
Management and quality of learning is very important in the effort to realize education. Effective learning quality management will be able to influence between teacher as facilitator and learner as subject in teaching learning. This research is to know the management and quality of learning Indonesian at State Junior High School 4 Rejang Lebong. In particular this study to describe: 1). How to manage learning planning in Indonesian language, 2). How to manage the implementation of Indonesian language learning, 3). How to evaluate Indonesian learning management, 4). How innovation is done in the management of learning Indonesian language. The method used is descriptive qualitative. Methods of data collection are interviews, observation and documentation. The quality of the study of quality management of Indonesian language learning, can be concluded to contribute to learning Indonesian language. The implication of this finding is that Indonesian teachers can understand quality management in applying learning. Keywords: Management, Quality, Learning Indonesian